International Liquidity Standards as Complementary Measures for Bank and Banking Sector Security - Chaikovska, Ivanna (Journal of Finance and Financial Law, 2022)
The purpose of the article is to assess the security of Polish listed banks and the entire banking sector in terms of their liquidity. This article characterizes the liquidity of the Polish banking sector and Polish listed banks in the years 2009–2019. Methodology. The analysis was based on post-crisis LCR and NSFR liquidity ratios. The calculations used the financial data provided by the Bank Focus database, the Polish Financial Supervision Authority and consolidated financial statements of Polish listed banks. To achieve the set objective were used methods of comparing documents and legal acts (especially in the part of the article concerning the characteristics of the international standards of liquidity) and the methods of descriptive statistics (in the empirical part of the article). Results of the research. The above analysis is the basis for the verification of the hypothesis that international liquidity standards increase the level of security of Polish listed banks and the entire banking sector.